Seni Jathilan dalam Dimensi Ruang dan Waktu - Kuswarsantyo Kuswarsantyo (Jurnal Kajian Seni, 2014)
After the launching of tourism in 1986 by President Suharto jathilan become more varied both in terms of presentation and story themes resources are taken. The development of the presentation is able to shift the initial function jathilan as part of the ritual as Merti village, rasullan, sedhekah sea, and the like are held regularly every year. Jathilan that there transformed into a commodity that is used as a tourist attraction. The presentation function jathilan now able to adapt to the needs of the community aestetic supporters, so that there are currently several categories jathilan; First jathilan ritual that we can only meet once a year for certain ceremonial events. Both jathilan entertainment, which can be encountered at any time when no one had a lavatory. And third jathilan for the festival. Jathilan festival is formatted with choreography and certain rules by the organizers